Tripeptides From Casein Are Signal Molecules to Induce the Expression of the Extracellular Protease MCP-01 Gene in Marine Bacterium Pseudoalteromonas sp. SM9913 - Chen, Xiu-Lan; Yang, Jin-Yu; Zheng, Xiao-Yu; Sheng, Qi; Wang, Lei; Zhang, Yu-Zhong; Qin, Qi-Long; Zhang, Xi-Ying (Frontiers in Microbiology, 2019)
Microbial extracellular proteases play crucial roles in marine protein degradation and nitrogen recycling. Although a large number of marine bacteria are found to produce extracellular proteases, it is still unknown how marine bacteria response to environmental proteins to activate the expression of genes encoding extracellular proteases. The inducing signal molecule for marine bacterial extracellular proteases has never been identified. In this study, we identified tripeptides as the inducing signal molecules for the extracellular protease MCP-01 of the deep-sea bacterium Pseudoalteromonas sp. SM9913. We found that casein, but not casamino acids, can induce the gene expression and synthesis of MCP-01, suggesting that peptides rather than amino acids derived from casein induce the gene expression and synthesis of MCP-01 in SM9913. Then, casein was hydrolyzed by SM9913 extracellular proteases, and the peptides with inducing effect were isolated and characterized. Finally, 4 tripeptides, SPP, RYP, RQF and FRQ, were shown to have significant inducing effect on the expression of MCP-01 gene, indicating that they are likely the inducing signal molecules for the expression of protease MCP-01 gene in SM9913. This study sheds light on the induction mechanism for the gene expression and biosynthesis of marine microbial extracellular proteases, which is helpful in better understanding the adaptation of bacteria to deep sea sedimental environment.